Child sexual abuse: forensic issues in evidence, impact, and management - Bryce, India; Petherick, Wayne (Academic Press, an imprint of Elsevier, 2020)
"Child Sexual Abuse: Forensic Issues in Evidence, Impact, and Management approaches the issue of child sexual abuse from several viewpoints. First, child abuse will be considered from both victimization and offending perspectives and, although empirical scholarship will inform much of the content, there will be applied material from experts and practitioners in the field - from policing to child safety to intelligence. This is a significant divergence from literature most commonly provided in the market. Additionally, contemporary scholarship on issues surrounding child abuse includes (but is not limited to) typologies (such as psychological, sexual and physical abuse, and neglect), risk and protective factors (at individual and community levels), recognition, responses, biopsychosocial outcomes (dealt with in discrete chapters), public policy, prevention, institutional abuse, children and corrections, treatment and management (including global comparisons), and myths and fallacies (e.g. outcomes for children of same-sex marriages)"--